The Double Fence: Overlapping Institutions and Deforestation in the Colombian Amazon (2020)
There is evidence that suggests that both the creation of Protected Areas (PAs) and indigenous Reserves (IRs) has helped to reduce deforestation. Nevertheless, there are some overlapping zones between these institutions in the Colombian Amazon that have not been studied. Are these overlaps affecting the deforestation in the IRs? How are the indigenous communities responding to these overlaps? In this paper I estimate the impacts of these overlaps on the deforestation inside the IRs using a Propensity Score Matching (PSM) methodology. I use important determinants of the location of PAs and deforestation to create a valid counterfactual within the IRs. My results suggest that the overlap significantly reduces the deforestation, but that there is a differential effect depending on the IR¿s size. These results suggest that the extra legal restrictionimposed by the central government, favor the territorial control inside the IRs. This paper provides a starting point to analyze the current relationship between the central government, the indigenous communities and how it affects deforestation.